Environmental factors affecting commuting accident in public university Kuantan, Pahang - Nor Azreen, Zabir (2018)
The purpose of this study is to identify factors that may cause commuting accident among staffs in Universiti Malaysia Pahang (UMP). The number of road accidents continues to grow rapidly every year in Malaysia. However, the unseen fact is the number of road victims mentioned is come from the commuting accident. According to the statistic from Social Organisation (SOCSO), number of industrial accidents is diminishing from 35,898 in 2013 and 35,294 in 2014 meanwhile the number of commuting accident rise up from 27,659 in 2013 and 28,037 in 2014. The objective of this study is to identify whether environmental factors is contributing to the commuting accident or not. The factors listed in this study are time of day, weather, road condition, road design, road lanes and infrastructure. Thus, a questionnaire is distributed among staffs in UMP to be answered by those who involved in accident from 2013 to 2017. Data from the questionnaires is analysed by using Statistical Package for the Social Sciences (SPSS) and the Spearman’s Rho method is used to find the correlation between environmental factors with commuting accident. The result shows that there is strong correlation between time of day with commuting accident which p-value (0.006). Therefore, the government and employer should propose some recommendations to decrease the number of commuting accidents.